(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The manipulation of digital images has become easy due to powerful computers, advanced photo-editing software packages and high-resolution image-capturing devices. The identification of image authenticity has received much attention because of the increasing power of image editing methods. Object removal is an image forgery technique, which is usually achieved by the Exemplar-Based Inpainting (EBI) method without any noticeable traces. Some legal issues may arise when a tampered image cannot be distinguished from a real one by visual examination. Therefore the manipulation of digital images has become a huge challenge to passive image forensics. There are a lot of forgery techniques that use to detect on these images after removing the object, but these techniques have limitations when used some post-processing operations such as super-resolution processing, noise addition, blurring and compression processes. To address this issue, this paper proposes a novel forgery detection technique to recognize tampered inpainting images, using topological data analysis (TDA) approach. TDA is a mathematical approach concern studying shapes or objects to gain information about connectivity and closeness property of those objects. This proposed technique is applied for a large number of natural images with getting a good results.